Efektifitas Bimbingan Kelompok Teknik Home Room untuk Meningkatkan Kohesivitas Kelompok - Ahmad Sa’id Mutohhari; Fakhruddin Mutakin; Yurike Kinanthy Karamoy (Program Studi Bimbingan dan Konseling FKIP Universitas Islam Jember, 2019)
This study was conducted to determine the extent of the effectiveness of home room engineering group guidance services to improve cohesiveness of students in class XII Science 2 of SMA Negeri 3 Jember. The research method used is an experimental method with one group pretest and posttest design research design. The method of determining the sample using purposive sampling, namely determining the sample based on specified criteria. Based on the results of the pretest conducted, obtained 6 counselees who will be the research sample. The data analysis method uses t-test analysis. This research was conducted by providing home room engineering group guidance services 5 times, with materials that have been prepared in accordance with indicators of cohesiveness and analysis of student needs. Based on the data analysis, the results of the t-test sig. (2-tailed) 0.00 <0.05. So Ha was accepted and Ho was rejected, with the conclusion that the home room engineering group guidance service was effective in increasing the cohesiveness of students of class XII Science 2 of SMA Negeri 3 Jember. Keywords: Home Room, Group Cohesiveness